In vitro thrombolytic, anthelmintic, anti-oxidant and cytotoxic activity with phytochemical screening of methanolic extract of Xanthium indicum leaves - Ghosh, Antara; Banik, Sujan; Islam, Md. Ariful (Bangladesh Journal of Pharmacology, 2015)
Xanthium indicum is an important medicinal plant traditionally used in Bangladesh as a folkloric treatment. The current study was undertaken to evaluate thrombolytic, anthelmintic, anti-oxidant, cytotoxic properties with phytochemical screening of methanolic extract of X. indicum leaves. The analysis of phytochemical screening confirmed the existence of phytosetrols and diterpenes. In thrombolytic assay, a significant clot lysis was observed at four concentrations of plant extract compare to the positive control streptokinase (30,000 IU, 15,000 IU) and negative control normal saline. The extract revealed potent anthelmintic activity at different concentrations. In anti-oxidant activity evaluation by two potential experiments namely total phenolic content determination and free radical scavenging assay by 2, 2-diphenylpicrylhydrazyl (DPPH), the leaves extract possess good anti-oxidant property. In the brine shrimp lethality bioassay, the crude extract showed potent (LC50 1.3 ?g/mL) cytotoxic activity compare to the vincristine sulfate as a positive control (LC50 0.8 ?g/mL).